Influence of Ethnicity, Age, and Time on Sex Disparities in Long‐Term Cause‐Specific Mortality After Acute Myocardial Infarction. Issue 10 (6th October 2016) - Gao, Fei; Lam, Carolyn S.P.; Yeo, Khung Keong; Machin, David; de Carvalho, Leonardo P.; Sim, Ling Ling; Koh, Tian Hai; Foo, David; Ong, Hean Yee; Tong, Khim Leng; Tan, Huay Cheem; Earnest, Arul; et al.
Abstract : Background: We examined the influence of sex, ethnicity, and time on competing cardiovascular and noncardiovascular causes of death following acute myocardial infarction in a multiethnic Asian cohort. Methods and Results: For 12 years, we followed a prospective nationwide cohort of 15 151 patients (aged 22–101 years, median age 63 years; 72.3% male; 66.7% Chinese, 19.8% Malay, 13.5% Indian) who were hospitalized for acute myocardial infarction between 2000 and 2005. There were 6463 deaths (4534 cardiovascular, 1929 noncardiovascular). Compared with men, women had a higher risk of cardiovascular death (age‐adjusted hazard ratio [HR] 1.3, 95% CI 1.2–1.4) but a similar risk of noncardiovascular death (HR 0.9, 95% CI 0.8–1.0). Sex differences in cardiovascular death varied by ethnicity, age, and time. Compared with Chinese women, Malay women had the greatest increased hazard of cardiovascular death (HR 1.4, 95% CI 1.2–1.6) and a marked imbalance in death due to heart failure or cardiomyopathy (HR 3.4 [95% CI 1.9–6.0] versus HR 1.5 [95% CI 0.6–3.6] for Indian women). Compared with same‐age Malay men, Malay women aged 22 to 49 years had a 2.5‐fold (95% CI 1.6–3.8) increased hazard of cardiovascular death. Sex disparities in cardiovascular death tapered over time, least among Chinese patients and most among Indian patients; the HR comparing cardiovascular death of Indian women and men decreased from 1.9 (95% CI 1.5–2.4) at 30 days to 0.9 (95% CI 0.5–1.6) at 10 years. Conclusion: Age, ethnicity, and time strongly influence the association between sex and specific cardiovascular causes of mortality, suggesting that health care policy to reduce sex disparities in acute myocardial infarction outcomes must consider the complex interplay of these 3 major modifying factors.